Mission as accompaniment : a response to mechanistic dehumanization - Konkol, Brian E. (FORTRESS Press, 2017)
Mission as accompaniment emerges from both Latin American theology and a development methodology; it involves "walking together in solidarity that practices interdependence and mutuality" and is thus viewed as a suitable foundation to counteract dehumanization. This study argues that mission as accompaniment has not yet offered an adequate response to mechanistic dehumanization. It argues further that two additional elements-the African concept of Ubuntu, and an Olive Agenda-when integrated into mission as accompaniment, will better equip church companions to respond more effectively to mechan.